2010
DOI: 10.1186/1476-072x-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Standardized observation of neighbourhood disorder: does it work in Canada?

Abstract: BackgroundThere is a growing body of evidence that where you live is important to your health. Despite numerous previous studies investigating the relationship between neighbourhood deprivation (and structure) and residents' health, the precise nature of this relationship remains unclear. Relatively few investigations have relied on direct observation of neighbourhoods, while those that have were developed primarily in US settings. Evaluation of the transferability of such tools to other contexts is an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The extent to which those findings apply to the Canadian context is unknown. For example, the concentrated poverty and high levels of urban social disorder documented in U.S. cities is present to a lesser degree in Canada (Sampson et al, 1997;Oreopoulos, 2008;Parsons et al, 2010). Yet, like many cities globally, income inequalities between neighbourhoods in Toronto have been widening for the past several decades (Oreopoulos, 2008;Hulchanski, 2010).…”
Section: Neighbourhood Effects On Health and Well-being (Nehw) Studymentioning
confidence: 99%
“…The extent to which those findings apply to the Canadian context is unknown. For example, the concentrated poverty and high levels of urban social disorder documented in U.S. cities is present to a lesser degree in Canada (Sampson et al, 1997;Oreopoulos, 2008;Parsons et al, 2010). Yet, like many cities globally, income inequalities between neighbourhoods in Toronto have been widening for the past several decades (Oreopoulos, 2008;Hulchanski, 2010).…”
Section: Neighbourhood Effects On Health and Well-being (Nehw) Studymentioning
confidence: 99%
“…Previous sociological research hypothesizing the influence of neighborhood social disorganization on various health outcomes resulted in the development of reliable methods for systematically assessing a range of neighborhood environments (Raudenbush & Sampson, 1999). Systematic Social Observation and similar types of instruments have subsequently been utilized to assess spatial effects in small scale settings (Bader et al, 2015; Cunningham-Myrie et al, 2015; Kwarteng, Schulz, Mentz, Zenk, & Opperman, 2014; Parsons et al, 2010; Schaefer-McDaniel, O'Brien Caughy, O'Campo, & Gearey, 2010). Although studies have indicated the importance of other types of micro-environments on health outcomes --for example, homes (Sirard, Laska, Patnode, Farbakhsh, & Lytle, 2010) or recreational facilities (Shores & West, 2008)—very few studies have attempted to systematically assess such micro-environments in a way that could be replicated.…”
Section: Discussionmentioning
confidence: 99%
“…Field tools have been used in health geography and criminology, albeit in different contexts and for different purposes than presented in this paper. One method that has been established is the use of checklists to inventory the variables of interest (Raudenbush and Sampson 1999;Parsons et al 2010;Chow et al 2014;Hwang and Sampson 2014;Morrison et al 2016;Lafontaine et al 2017). These studies illustrate how field tools and visual information can be used; they still, however, need to be adapted considerably for our present purposes.…”
Section: Literature Reviewmentioning
confidence: 99%